Comparisons between different fire ants control methods in urban environments - Elisa Furtado Fernandes; Helba H Santos-Prezoto; Raquel Mendonça; Mariana Monteiro de Castro; Odair Correia Bueno; Fábio Prezoto (Annals of Environmental Science and Toxicology - Peertechz Publications, 2020)
Many homemade methods are recommended for the control of fire ants, but the choice of a control method for this ants in the urban environment is necessary in view of the damage they have caused to the environment and human health. Thus, the objective of this work was to compare the efficiency of chemical (liquid insecticide and granular insecticide) and homemade (hot water and detergent water) methods used to control these ants in urban gardens. The study was conducted in the city of Juiz de Fora, MG, Brazil. The treatments were applied only once on Solenopsis saevissima colonies: (T1) Hot water, (T2) Water with detergente, (T3) Liquid insecticide and (T4) Granular inseticide. To determine the amount of applied product in T1, T2 and T3 treatments, colonies were selected by linear size and for treatment T4, colonies were classified by volume. the colonies were monitored monthly for four consecutive months (July to October) to evaluate the effectiveness of the control method employed. The treatments presented distinct performances in fire ants control in urban area, being the liquid insecticide the most efficient in eliminating the colonies. With this study we were able to evaluate the impacts caused by each treatment, as well as the pros and cons of using each one of them, and finally, we suggest an efficient fire ants control method with lower cost per colony and less impact on the environment.